Web-Based Monitoring and Evaluation: Research Activity Assessment Case Study - Cherednichenko, Olga; Yanholenko, Olha; Iakovleva, Olena (EDIS Publishing Institution of the University of Zilina, 2013)
The work is devoted to issues of monitoring and evaluation system development. It is suggested to use the web as the source of data for monitoring. The assessment of web-based indicators for monitoring is realized with the help of Rasch model. The application of suggested approach is illustrated by the case study of universities research activity assessment.
Keywords: web mining; research activity; information system; Rasch model